Advances in Numerical Modeling of Adhesive Joints - da Silva, Lucas Filipe Martins; Campilho, Raul D. S. G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book deals with the most recent numerical modeling of adhesive joints. Advances in damage mechanics and extended finite element method are described in the context of the Finite Element method with examples of application. The book also introduces the classical continuum mechanics and fracture mechanics approach and discusses the boundary element method and the finite difference method with indication of the cases they are most adapted to. At the moment there a no numerical technique that can solve any problem and the analyst needs to be aware of the limitations involved in each case.
Introduction -- Finite element method -- Boundary element method -- Finite difference method -- Conclusions.
Keywords: Engineering; Materials; Structural control (Engineering).; Surfaces (Physics).; Engineering; Continuum Mechanics and Mechanics of Materials; Surfaces and Interfaces, Thin Films; Operating Procedures, Materials Treatment